The Integrative Method “Suture Dragging and Simplified Vacuum Assisted Therapy” for Complex Pilonidal Sinus Disease - Chen Wang; YiBo Yao; YongQing Cao (Case Reports in Surgery)
Complex and recurrent pilonidal sinuses are best treated with surgery. Different surgical modalities as complete excision of the pilonidal sinus leave the wound open or procedures like closing the wound with or without reconstructive flap are widely used. The open procedure is radical but may cause broad excision and prolonged morbidity, while risk of infection and rate of recurrence are higher in the closed techniques. Traditional Chinese surgical treatments are less invasive and more effective; they have been used to treat sinus and fistula disease successfully. In this case report, we have described a male adolescent with complex pilonidal sinus, who received traditional Chinese surgical treatment combined with modern wound healing technique. He recovered completely with short hospitalization, good tolerance, less pain, and scarring. Therefore, we recommend using this integrative method to treat complex pilonidal sinus disease.